Clozapine Withdrawal-Induced Malignant Catatonia or Neuroleptic Malignant Syndrome: A Case Report and a Brief Review of the Literature. Issue 4 (16th July 2021) - Belteczki, Zsuzsanna; Ujvari, Julia; Dome, Peter
Abstract: In our brief literature review, we discuss the changes in the concept of catatonia as well as its various types and symptoms. We also succinctly review the possible symptoms of clozapine withdrawal. In addition, we analyze the main features of the very few published cases of clozapine withdrawal-induced catatonia and the relationship between neuroleptic malignant syndrome and the malignant subtype of catatonia. Furthermore, we present the case of a 29-year-old male patient with schizophrenia in whom a malignant catatonic episode/neuroleptic malignant syndrome (with negativism, stupor, mutism, autonomic signs [eg, fever, hyperhidrosis], and elevated creatine kinase levels) began 5 days after the patient decided arbitrarily to cease his clozapine treatment. His catatonic symptoms quickly (ie, within a few days) resolved after the reinstitution of clozapine. Finally, we attempt to provide a theoretical explanation for the surprising finding in the literature that the withdrawal of clozapine, unlike the withdrawal of any other antipsychotics, may be associated with catatonia (frequently its malignant subtype). The take-home message of our case is that clinicians should bear in mind the risk of catatonia (especially the malignant subtype of it) after the prompt withdrawal of clozapine therapy.